2008
DOI: 10.1021/bm800049w
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of the Amorphous Cellulose in Cotton-Based Paper

Abstract: Hydrolysis of cellulose in Whatman no. 42 cotton-based paper was studied using gel permeation chromatography (GPC), electrospray ionization-mass spectrometry (ESI-MS), and uniaxial tensile testing to understand the course and kinetics of the reaction. GPC results suggested that scission reactions passed through three stages. Additionally, the evolution of soluble oligomers in the ESI-MS data and the steady course of strength loss showed that the hydrolysis reaction occurred at a constant rate. These findings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 34 publications
(45 reference statements)
4
47
0
2
Order By: Relevance
“…This is consistent with the much higher accessibility of amorphous cellulose in comparison to the crystalline domains of the cellulose (Hong et al 2007;Park et al 2010;Yu and Wu 2010). Stephens et al (2008b) likewise showed that amorphous cellulose was more susceptible to acid hydrolysis. Such attack, when it occurs in within paper, has the potential to destroy connections between the crystalline regions within fibers (Whitmore 2011), in addition to some of the bonded areas between fibers in paper.…”
Section: Meniscus Retraction and Concentration Of Solutessupporting
confidence: 79%
“…This is consistent with the much higher accessibility of amorphous cellulose in comparison to the crystalline domains of the cellulose (Hong et al 2007;Park et al 2010;Yu and Wu 2010). Stephens et al (2008b) likewise showed that amorphous cellulose was more susceptible to acid hydrolysis. Such attack, when it occurs in within paper, has the potential to destroy connections between the crystalline regions within fibers (Whitmore 2011), in addition to some of the bonded areas between fibers in paper.…”
Section: Meniscus Retraction and Concentration Of Solutessupporting
confidence: 79%
“…an initial hydrolysis of the amorphous region which is more easily accessed by the solvent and a latter hydrolytic attack of the crystalline portion [31,32]. Previous researchers reported that one of the most important types of compounds present in bio-oil obtained from hydrothermal liquefaction of biomass were weak acids such as acetic acid, formic acid, and levulinic acid [5,6,9].…”
Section: Investigation Of Presumed Hydrothermal Liquefaction Mechanismmentioning
confidence: 99%
“…41 The slope k′ in the plot (1/M nt -1/M nt0 ) as a function of time t is the reaction rate constant. According to this model, the relationship between (1/M nt -1/M nt0 ) and aging time t should be linear.…”
Section: Hydroperoxides In Aged Papermentioning
confidence: 99%